2018
DOI: 10.1007/s00405-018-4943-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging evaluation of electrode placement and effect on electrode discrimination on different cochlear implant electrode arrays

Abstract: The aim of the present study is to evaluate the effect of electrode discrimination based on electrode to modiolus distance in different cochlear implant models, using image information to estimate the outcomes after an implantation on electrode discrimination METHODS: A descriptive prospective randomized study performed during 16 months. A psychoacoustic platform was used to evaluate patients' electrode discrimination capabilities of patients. For the acquisition of the images, a cone beam computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Positioning the cochlear implant electrode contacts close to the stimulation target reduces the current spread and leads to more focused stimulation; thus, lowering the current levels required to produce behavioural thresholds and comfort levels [12][13][14]. This localized stimulation provides superior place-pitch spectral discrimination [15,16], and improved speech perception outcomes [17,18]. However, due to their increased stiffness and size, perimodiolar arrays which use stylets to keep them straight at the point of insertion, have been associated with poorer hearing preservation results and a higher incidence of basilar membrane trauma compared to thin, flexible lateral wall arrays [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Positioning the cochlear implant electrode contacts close to the stimulation target reduces the current spread and leads to more focused stimulation; thus, lowering the current levels required to produce behavioural thresholds and comfort levels [12][13][14]. This localized stimulation provides superior place-pitch spectral discrimination [15,16], and improved speech perception outcomes [17,18]. However, due to their increased stiffness and size, perimodiolar arrays which use stylets to keep them straight at the point of insertion, have been associated with poorer hearing preservation results and a higher incidence of basilar membrane trauma compared to thin, flexible lateral wall arrays [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In a pitch ranking task, the subject is typically asked to judge which of the stimulating electrode contacts has a higher pitch. Several studies based on pitch ranking tasks showed a positive relationship between the ability to distinguish pitches and speech perception (Nelson et al 1995;Collins, Zwolan, and Wakefield 1997). Furthermore, Kenway et al (2015) found that pitch ranking ability is an independent predictor of overall CI outcome.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, cochlear implant recipients with slim modiolar electrodes (i.e., CI532/632) led to either similar or statistically superior audiological results compared with those with straight electrodes (i.e., CI422/522) strictly matched for age and preoperative hearing thresholds 2 . Furthermore, a growing body of evidence suggests that the enhanced modiolar proximity of slim modiolar electrodes would lead to improved place-pitch spectral discrimination 16 , and speech perception outcomes 14 , 17 , as compared with conventional perimodiolar electrodes. However, not all reports in literature fully support this phenomenon 9 , 18 , 19 , probably due to confounding variables such as heterogeneous degrees of modiolar proximity even with slim modiolar electrodes 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, not all reports in literature fully support this phenomenon 9 , 18 , 19 , probably due to confounding variables such as heterogeneous degrees of modiolar proximity even with slim modiolar electrodes 20 . Indeed, better modiolar proximity has been proposed to attenuate the substantial overlap (i.e., spread of excitation) in the electrical field between electrode contacts, resulting in better electrode discrimination capability 16 , 21 , and potentially better speech outcomes than conventional electrodes 21 . In addition, positioning of the electrodes close to the spiral ganglion neurons can reduce the effects of neural-electrode interaction by improving channel discrimination 16 , lowering threshold levels 22 , and reduction of power consumption 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation